Pengaturan tentang Kewajiban Pembacaan Akta Oleh Notaris Kepada Penghadap Tuna Rungu - Umar Hasan; Syamsir; Muhammad Kaisar Irsandy Arfa (Jurnal Hukum Lex Generalis, 2024)
Arrangements on the Obligation to Read Deed by Notaries to Deaf Client and to find out and analyze future Arrangements on Procedures for Reading Deed by Notaries to Deaf Client. Normative juridical is "normative jurisprudence is a science of law that is sui generic". The type of normative legal research is in the form of an "inventory of applicable legislation, seeking to find the principles or philosophical basis of the laws and regulations, or research in the form of efforts to discover laws that are appropriate to the level of regulation that provides the same treatment for deaf people in the drafting of Notary deeds in articles. The mechanism for the issuance of notarized deeds submitted by deaf persons already exists and can be referred to as a reference in making notary deeds, then notary deeds can be made with this mechanism. Legal support against the deaf in the text of the Notarіs deed. The regulation on the obligation to read the deed by a notary to the deaf person has not been accommodated, there is an ambiguity in the norm in Article 43 paragraph (2) of the UUJN-P, where Article 43 paragraph (2) of the UUJN-P does not provide a detailed explanation regarding the person who does not understand the language. Future arrangements regarding the procedure for reading the deed by a notary to a deaf person against Article 43 paragraph (2) of the UUJN-P need to be clarified.